KAJIAN KESESUAIAN LAHAN UNTUK MENDUKUNG PENGEMBANGAN KOMODITAS PERTANIAN DI WILAYAH PERBATASAN NEGARA REPUBLIK INDONESIA (Studi Kasus di Kabupaten Merauke, Provinsi Papua) - Marfai, Muh. Aris; Cahyadi, Ahmad (Bumi Lestari, 2012)
This research aims to analyze the land suitability in the national border on Olikobel District, Merauke District, Sota District, and Naukenjarai District which are located in the eastern national border of Indonesia. Land suitability analysis conducted in this research is focused for the rice farming and rubber planting. Using the land unit as the basic of the analysis and the required characteristics of the area for growing the plants, comparison study has been done to match the land condition and its requirement to grow. The result of this research has shown various land suitability for growing the plants. For rubber plant, the best location for growing is located in the Sota and Olikobel District, which area extends of 140,942.5 hectares. Due to the drainage and flooding, several parts of the research area are considered has low suitability to grow the rubber plants. As the results, various classes of land suitability for rubber plants consist of S1, S2b, S2se, S3wf, Nwf dan Nwft are found in the research area. For rice farming, Marauke District is considered has the most suitable area to grow the rice, in which the area extends for 9,948.52 hectares. Drainage and flooding also becomes the limitation factor of the land suitability, causing various classes of land suitability for rice farming, namely: S1, S3w, S3wt, S3ws, S3wse, S3wtse, Nt, Nws dan Nwt. Therefore, proposed method in drainage management area is required. With the improvement in the soil drainage is predicted to increase the extents of most suitable area (S1) to be 147,883.28 hectares.
Keywords: National Border; Merauke; Land Suitability; Rice Farming; Rubber Planting